Effect of Roux‐en‐Y gastric bypass on the pharmacokinetic‐pharmacodynamic relationships of liquid and controlled‐release formulations of oxycodone. Issue 3 (12th July 2021) - Ladebo, Louise; Abuhelwa, Ahmad Y.; Foster, David J. R.; Kroustrup, Jens P.; Pacyk, Grzegorz J.; Kongstad, Kenneth T.; Drewes, Asbjørn M.; Christrup, Lona L.; Olesen, Anne E.
Abstract: The physiological changes following Roux‐en‐Y gastric bypass (RYGB) surgery may impact drug release from mechanistically different controlled‐release tablets, making generic substitution inappropriate. This study aimed to characterise the pharmacokinetic‐pharmacodynamic relationships of oxycodone from a lipid‐based and water‐swellable controlled‐release tablet in RYGB patients. Twenty RYGB patients received 10‐mg oral solution oxycodone or 20‐mg controlled‐release (water‐swellable or lipid‐based) oxycodone in a three‐way, randomised, semiblinded and cross‐over study. Blood sampling and pupillary recordings were conducted over a 24‐h period. A previously established pharmacokinetic‐pharmacodynamic model of these three formulations in healthy volunteers was used in the analysis as a reference model. No differences in absorption kinetics were seen between controlled‐release formulations in patients. However, the absorption lag time was 11.5 min in patients vs 14 min in healthy volunteers for controlled‐release tablets ( P < 0.001). Furthermore, oral bioavailability was 14.4% higher in patients compared to healthy volunteers regardless of formulation type ( P < 0.001). Oxycodone pharmacodynamics were not significantly affected by formulation or patient status. However, baseline pupil diameter was inversely correlated with age ( P < 0.001) and plasma concentrations of oxycodone at half‐maximum effect were 31% lower in males compared to females ( P < 0.05). Generic substitution of monophasic lipid‐based and water‐swellable controlled‐release oxycodone tablets may be considered safe in RYGB patients.